Correlation of Handgrip Strength with Thumb Flexibility, Strength and Pain in Manual Therapists - Riaz, Saba; Mazhar, Tooba; Riaz, Sumbal; Batool, Ayesha; Khan, Awishba; Khan, Sadia (Pakistan Armed Forces Medical Journal, 2023)
Objective: To find the correlation bwteen hand grip strength with thumb muscle strength, flexibility and thumb pain in manual therapists and to find out the variation of these variables in healthy manual therapists.Study Design: Comparative cross-sectional Study.Place and Duration of Study: Pakistan Society of Rehabilitation and Disability, Jinnah Hospital, Ittefaq Hospital, and Riphah University Pakistan, from Nov 2021 to Jan 2022.Methodology: One hundred thirty-five manual therapists were enrolled. Informed consent was taken from participants meeting inclusion and exclusion criteria. The questionnaire was filled out using a Dynamometer for Handgrip strength check, a Manual Muscle testing technique for Thumb muscle strength check, a Numeric pain rating scale for Pain intensity, and Goniometry for Flexibility of the Thumb muscles.Results: Results showed that most manual therapists had no wrist pain (99,73.3%) or thumb pain (104,77%). The majority of therapists (116 ,85.9%), had less than normal grip strength of hand, and 58(43%) had maximum thumb strength. There was a positive correlation between grip strength and thumb strength (r=0.234). There was a negative correlation between grip strength and thumb pain (r=-0.077).Conclusion: The study concluded that most manual therapists did not suffer from wrist and thumb pain. The majority had good thumb muscle strength but poor hand grip strength. Thumb strength positively correlates with grip strength, while thumb pain negatively correlates with handgrip strength.